Galectin-3 is induced in rheumatoid arthritis synovial fibroblasts after adhesion to cartilage oligomeric matrix protein. Issue 3 (2nd September 2004) - Neidhart, M; Zaucke, F; von Knoch, R; Jüngel, A; Michel, B A; Gay, R E; Gay, S
Abstract : Background: Galectin-3 is expressed in the synovial tissue of patients with rheumatoid arthritis (RA), particularly at sites of joint destruction. Objective: To explore the possibilities that galectin-3 is induced either by proinflammatory cytokines or by adhesion to cartilage components. Methods: Cell culture plates were coated with fibronectin, collagens I–VI, or cartilage oligomeric matrix protein (COMP), and the suspended cells were then added. The medium was changed after 1 hour at 37°C. Adherent cells were further incubated for 18 hours in the presence or absence of tumour necrosis factor α (TNFα) or interleukin 1β. Cells were pretreated with murine IgG1, anti-CD29, -CD51, -CD61 (integrins), or -CD3 monoclonal antibodies and transferred to culture plates coated with COMP. Adherent cells were counted by light microscopy. The expression of intracellular galectin-3, or cell surface CD29, CD51, and CD61 was determined by flow cytometry before and after adhesion. Results: Four times more RA synovial fibroblasts (SF) than osteoarthritis SF adhered to COMP. RA SF presented more cell surface integrins, and monoclonal antibodies against CD51 inhibited the adhesion to COMP by 80%. TNFα reduced the expression of CD61 and the adhesion to COMP, but did not reverse the adhesion once it had taken place. The adhesion of RA SF to COMP was found to increase the intracellular level of galectin-3. In contrast, intracellular galectin-3 decreased after exposure to TNFα. Conclusion: The increase of galectin-3 occurs after adhesion to COMP, and the αVβ3 receptor (CD51/CD61) has a pivotal role in this process.